Features of Periodontal Status and Oral Hygiene in Adolescents with Hyperandrogenism - Bilynskyi Олександр; Bilynska Віталія; Izay Мілан; Hanhur Іван; Stoyka Василь (Actual Dentistry, 2026)
Introduction. The prevalence of gingival and periodontal diseases among adolescents is steadily increasing. Hormonal changes are recognized as one of the contributing factors to inflammation in periodontal tissues. Investigating such risk factors may enhance preventive strategies for these conditions. Aim. To evaluate the influence of female sex hormones on periodontal tissue status in adolescents during puberty. Materials and Methods. A dental examination was conducted on 76 girls at the university dental clinic. Gingival inflammation was assessed using the Gingivitis Index (GI, Silness–Löe). Dental plaque was evaluated using the Simplified Oral Hygiene Index (OHI-S, Green–Vermillion). Blood levels of sex hormones (free testosterone index, DHEA, 17-OH progesterone, and androstenedione) were measured under fasting conditions on days 2–5 of the menstrual cycle. Statistical analysis was performed using standard methods of variational statistics. Conclusion. The findings indicate that during puberty, particular attention should be directed to periodontal health and oral hygiene, as changes in hormonal status exert a significant impact on these parameters.